2020
DOI: 10.1371/journal.pntd.0008959
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chironomid species as natural reservoirs of toxigenic Vibrio cholerae strains with pandemic potential

Abstract: Vibrio cholerae causes the fatal cholera diarrhea. Chironomids (Diptera; Chironomidae) are abundant in freshwater aquatic habitats and estuaries and are natural reservoirs of V. cholerae. Until now, only the non-O1/O139 serogroups of V. cholerae were identified in chironomids. Here, we explored whether chironomids are natural reservoirs of V. cholerae O1/O139 serogroups, which are associated with cholera endemics and pandemics. All four life stages of chironomids were sampled from two rivers, and a laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Recently, Vibrio and Aeromonas were suggested to serve as C. transvaalensis symbionts [ 15 ]. Moreover, toxigenic V. choerae O1 and O139 were previously detected in C. ramosus larvae [ 16 ]. In the current study, we confirmed these findings by identifying Vibrio and Aeromonas in larvae that were sampled both from the laboratory culture and the Mutha River, using both 16S rRNA gene sequencing and metagenomics methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Vibrio and Aeromonas were suggested to serve as C. transvaalensis symbionts [ 15 ]. Moreover, toxigenic V. choerae O1 and O139 were previously detected in C. ramosus larvae [ 16 ]. In the current study, we confirmed these findings by identifying Vibrio and Aeromonas in larvae that were sampled both from the laboratory culture and the Mutha River, using both 16S rRNA gene sequencing and metagenomics methods.…”
Section: Discussionmentioning
confidence: 99%
“…Chironomid larvae were sampled in November 2018 from (i) the Mutha River, Pune, India (18.2901° N, 73.4956° E), and (ii) a laboratory culture which was initially collected from the Mula River, Pune, India (18.5551° N, 73.8618° E), in April 2018, and maintained under laboratory conditions for eight months until it was sampled for our current study. The sampling procedure and the conditions for rearing the laboratory culture were previously described, in detail, by Laviad-Shitrit et al [ 16 ]. In total, 31 larvae that were identified as C. ramosus were selected for further analyses in the current study ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…C. circumdatus egg masses, larvae, and pupae were collected in November 2018 from plants (Eichhornia crassipes) and riverbank sediments from urban settings surrounding two rivers in Pune, India: (i) the Mula River (18.5551 • N, 73.8618 • E) and (ii) the Mutha River (18.2901 • N, 73.4956 • E) (Laviad-Shitrit et al, 2020). Samples were also collected from (iii) laboratory cultures being reared in the Animal House Facility at the Department of Zoology, SPPU, Pune, India.…”
Section: Chironomus Circumdatus Samplingmentioning
confidence: 99%
“…All the samples that were investigated in the current study were taxonomically identified as C. circumdatus by Laviad-Shitrit et al (2020). Each sample was treated individually after collection by washing it five times in 1 ml sterile water to remove the microorganisms that were not tightly connected to the samples.…”
Section: Chironomus Circumdatus Samplingmentioning
confidence: 99%
See 1 more Smart Citation